1987
DOI: 10.1002/mrd.1120160207
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization with normal development in the sheep

Abstract: Ovine tubal (n = 87) and ovarian in vitro matured oocytes (n = 99) were fertilized in vitro with ejaculated spermatozoa capacitated for 8 h in modified defined medium buffered with Hepes. High levels of fertilization were obtained as assessed by development to two- to six-cell stage within 40 h (75.8% for ovulated and 62.6% for in vitro matured oocytes). Electron microscope analysis of oocytes 20-22 h after insemination indicated that in vitro fertilization approximated the in vivo events. Embryos (two- to six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
8

Year Published

1987
1987
2000
2000

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 18 publications
1
27
0
8
Order By: Relevance
“…Good results have been reported at 38.5"C (Crozet et al, 1987). Sperm incubation temperatures, 22°C or 38.5"C, for 5 h were not associated with significant differences (P < 0.05) in fertilization rates but viability was positively affected subsequently by sperm incubation at 38.5"C, at least under the best conditions used in the present work (Table 2).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Good results have been reported at 38.5"C (Crozet et al, 1987). Sperm incubation temperatures, 22°C or 38.5"C, for 5 h were not associated with significant differences (P < 0.05) in fertilization rates but viability was positively affected subsequently by sperm incubation at 38.5"C, at least under the best conditions used in the present work (Table 2).…”
Section: Discussionsupporting
confidence: 60%
“…A maturation interval of 27 h was found to be superior for caprine oocytes (DeSmedt et al, 1992;Keskintepe et al, 1993;Martin0 et al, 1994). The best insemination intervals for mammalian IVMFC were indicated as 24 h for bovine (Younis et al, 19911, 18 h for sheep (Crozet et al, 1987), and 18-24 h for goat (DeSmedt et al, 1992, Keskintepe et al, 1993. The results presented here lanta, GA.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, the semen was resuspended in medium containing oestrus sheep serum. This serum supplementation was also used by Crozet et al [29] and still remains the most effective capacitating factor in sheep. Later, Pugh and co-workers [85] reported the birth of the first lambs following IVM [18].…”
Section: In Vitro Fertilizationmentioning
confidence: 93%
“…The successful co-culture of cumulus-enclosed oocytes and granulosa cells have proved the basic role of these cells in the acquisition of oocyte cytoplasmic competence at the final stages of its maturation (rabbit, Motlik and Fulka, 1982 ;ovine, Staigmiller and Moor, 1984 ;Crozet et aL, 1987 ;bovine, Critser et aL, 1986 Osborn, 1983 ;Osborn and Moor, 1983). This conclusion fits well with the observations of Soupart (1975) who showed that normal male pronucleus formation only occurred in human oocytes when estradiol and then estradiol plus 17 aOH progesterone were added sequentially in the culture medium.…”
mentioning
confidence: 99%